Child Maltreatment Fatalities in the United States : Four Decades of Policy, Program, and Professional Responses - Douglas, Emily M. (Springer Netherlands : Imprint: Springer, 2017)
This book focuses on the prevention of child abuse and neglect deaths in the U.S. In 2013 1,520 children died from maltreatment. This book defines child maltreatment fatalities (CMFs) and discusses the prevalence of deaths in the U.S. over the last several decades. It addresses the known risk factors for maltreatment deaths including child, parent, the parent-child relationship, and household risk factors. The main focus of the book addresses the responses and interventions that have been put in place in order to prevent CMFs: the child welfare profession, child death review teams, safe haven laws, criminal justice responses, public education, and new, federal efforts in the U.S. to reduce CMFs in the U.S. The book finishes by making recommendations for researchers, practitioners, and decision-makers about how to prevent fatal maltreatment among children in the U.S.
Keywords: Social sciences.; Maternal and child health services.; Social work.; Child psychology.; School psychology.; elektronické knihy; electronic books